Formation of Acetals and Ketals from Carbonyl Compounds: A New and Highly Efficient Method Inspired by Cationic Palladium - Mensah, Enoch A.; Green, Shawn D.; West, Jesse; Kindoll, Tyler; Lazaro-Martinez, Brenda (Synlett, 2019)
The development of a new, highly efficient, and simple method for masking carbonyl groups as acetals and ketals is described. This methodology relies on the nature of the palladium catalyst to direct the acetalization/ketalization reaction. This new protocol is mild and proceed with a very low catalyst loading at ambient temperatures. The method has been extended to a wide variety of different carbonyl compounds with various steric encumbrances to form the corresponding acetals and ketals in excellent yields.
Keywords: palladium catalysis; acetals; ketals; acetalization; ketalization; orthoformates